Mitochondrial Dynamics in the Brain Are Associated With Feeding, Glucose Homeostasis, and Whole-Body Metabolism - Haigh, Jessica L.; New, Lauryn E.; Filippi, Beatrice M. (Frontiers in Endocrinology, 2020)
The brain is responsible for maintaining whole-body energy homeostasis by changing energy input and availability. The hypothalamus and dorsal vagal complex (DVC) are the primary sites of metabolic control, able to sense both hormones and nutrients and adapt metabolism accordingly. Mitochondria respond to the level of nutrient availability by fusion or fission to maintain homeostasis, however, these processes can be disrupted by metabolic diseases including obesity and type II diabetes (T2D). Mitochondrial dynamics are crucial in the development and maintenance of obesity and T2D, playing a role in the control of glucose homeostasis and whole-body metabolism across neurones and glia in the hypothalamus and DVC.